2013
DOI: 10.1021/am404226e
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Synthesis of a Copper Ink for the Intense Pulsed Light Sintering of Conductive Copper Films

Abstract: Conducting films are becoming increasingly important for the printed electronics industry with applications in various technologies including antennas, RFID tags, photovoltaics, flexible electronics, and displays. To date, expensive noble metals have been utilized in these conductive films, which ultimately increases the cost. In the present work, more economically viable copper based conducting films have been developed for both glass and flexible PET substrates, using copper and copper oxide nanoparticles. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 28 publications
4
88
0
Order By: Relevance
“…However, Cu nanoparticle inks generally require high sintering temperatures above 300°C to obtain high conductivities [13,14]. To address this problem, photonic sintering using intense pulsed light with millisecond exposure times and a wide range of wavelengths has been reported as the most useful sintering method for the Cu nanoparticles [15][16][17][18]. A Cu nanoparticle layer can be converted to a highly conductive layer due to instantaneous heat generation within the layer accompanied by absorption of the intense pulsed light.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Cu nanoparticle inks generally require high sintering temperatures above 300°C to obtain high conductivities [13,14]. To address this problem, photonic sintering using intense pulsed light with millisecond exposure times and a wide range of wavelengths has been reported as the most useful sintering method for the Cu nanoparticles [15][16][17][18]. A Cu nanoparticle layer can be converted to a highly conductive layer due to instantaneous heat generation within the layer accompanied by absorption of the intense pulsed light.…”
Section: Introductionmentioning
confidence: 99%
“…Some research groups have reported improvements in layer conductivity or the reduction of sintering temperature for Cu nanoparticles, however they have focused on the application to interconnect technologies on flexible polymer film at low temperatures [15][16][17][18]. There have been few reports on the application of the printed Cu electrodes to TFT [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…To counter oxidation, the synthesis/deposition of copper nanoparticles used harsh reducing agents of hydrazine 164 and sodium borohydride 78,106 . Additives such as PVP 85 or CTAB 165 can increase the solution stability and control the particle size of the copper nanoparticles, but there is an inherent tradeoff when adding large molecules and polymers on the resulting porosity/conductivity of IPL processed films.…”
Section: Reduction and Processing Methodsmentioning
confidence: 99%
“…The synthesis of a copper dispersion by the reduction of Tergitol capped Cu 2+ ions using NaBH4 solution has been described in an earlier work. 106 For the synthesis, 5 ml of Tergitol NP-9 was added to a 50 ml aqueous solution of 0.1 M Cu(NO3)2, followed by 100 ml of Ethylene glycol. The pH of the solution was adjusted from pH 7 to 11 by the dropwise addition of NH4OH.…”
Section: Reduction and Processing Methodsmentioning
confidence: 99%
See 1 more Smart Citation